The effect of share exchange ratios on the wealth of participating firms involved in mergers - R. C. Van Den Honert; G. D.I. Barr; A. J. Galloway (South African Journal of Business Management, 1989)
A mathematical model which relates the exchange ratio (the number of acquiring firm's shares Issued for each target share) and the postmerger expected price earnings ratio of firms involved in mergers, is applied to 30 firms involved in recent share-exchange mergers on the Johannesburg Stock Exchange. It is found that about 70% of the mergers in the sample could be defined as rational, i.e. both shareholder parties gained in wealth. On the other hand, between 3% and 17% of the mergers led to a loss in wealth for both shareholder parties. Considering each party alone, between 70% and 80% of acquiring firms gained after merger, whilst for target firms 80% to 90% gained. It is also shown that the larger the target relative to the acquirer, the greater the share of the merger gains accumulating to the target.
Keywords: 650